Design and Production of Textile Fabrics Waste from Sudanese Garment Factories - Abdalgadir, Enas Elfatih ELmahi; Asad, Rabie Ahmed Mohammed; Elabid, Amel; Shibraen, Mahmoud H. M. A.; Esmaeel, Abdalla (Gezira Journal of Engineering and Applied Sciences, 2022)
The textile and apparel industry is one of the most significant industrial sectors in the world, however, it generates a large number of textiles and apparel waste before and after consumers' using. This study is conducted on the reusing and recycling of garment fabric waste in Sudanese garment factories and aimed to identify the causes of this waste and try to increase their economy, by collecting and reusing this waste to produce useful products. The problem was identified and working on solving it after observing the amount of fabric waste accumulated in the Sudanese garment factories, various tailors stores, and other tailors in the markets. Many several methods were used to reach these objectives, including observation and interviews with workers in this field, then conducted a questionnaire for them to help in the primary data collection. After collecting waste from different sources it was sorted and classified into subcategories, then many tests were done to obtained fabric pieces with a good quality. In the last step many designs were done by making a several patterns matched to the size and type of fabric, and the final products are (children’s clothes, bags, bedsheets, and other textiles), these products were presented to people who specialize in textile and garment industry to know their opinions about them and if it will benefit the society. From the results of this study, we found that the different garments that were produced from waste fabrics showed to have a great satisfaction among consumers. KEYWORDS: Textiles, Garments, Waste, Reusing, Recycling, Textile waste, Pattern, Design.